Tourism in Samarinda City, East Kalimantan : Recent Status and Future Directions - Mardiany Mardiany (Journal of Indonesian Tourism and Development Studies, 2017)
Tourism in Samarinda city, East Kalimantan, has been growing significantly and provides opportunities to develop as an alternative economic earning of city government and city dwellers. It is especially important to reduce mining activity and promotes more sustainable economic activity in Samarinda. The aims of the research were to identify the tourism potentials in Samarinda and discuss the opportunities for future tourism development. Research finds that basically tourism in Samarinda city grows significantly, following the growth of tourism in East Kalimantan Province. As a capital city, the basic infrastructure and amenity to support tourism are available in numerous form. There are also tourism attractions distributed in Samarinda city, ranging from natural, cultural and man-made attraction. These provide potentiality for Samarinda city to transform the regional policy in development, with put tourism is one of the main machines for future economic growth.Keywords: mining, sustainable tourism, tropical forest, urban development